Service Quality Rumah Sakit dan Efeknya terhadap Patient Satisfaction, Perceived Value, Trust, dan Behavioral Intention - Sandra Hendhana; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACTThis study examines the factors that affect patient's behavioral intention, with patient satisfaction, perceived value, and trust as intervening variables, as well as service quality as an independent variable. Service quality variable using the five dimensions that was first proposed by Parasuraman et al. (1985). The dimensions are tangibility, reliability, responsiveness, assurance, and empathy.            The population used in this study were inpatients at Siloam Hospital Bali, with a total sample of 155 patients. Data were collected by using questionnaire. The sampling method in this study using a type of non-probability sampling with combination method: purposive sampling-accidental sampling-quota sampling. The analysis technique used to analyze the data is SEM (Structural Equation Model).            Squared Multiple Correlations results indicate that behavioral intention variables are influenced by patient satisfaction, perceived value, trust, and service quality. Patient satisfaction is influenced by service quality. Perceived value is influenced by service quality, while trust affected by service quality. Service quality, patient satisfaction, and trust, positively significant affect behavioral intention.            The conclusion of this research is service quality has a significant positive effect on patient satisfaction, perceived value, trust and behavioral intention patients. Patient satisfaction and trust has a significant positive effect on the patient's behavioral intention. While the perceived value has a negative effect on the patient's behavioral intention. This study is useful for Siloam Hospitals Bali management and other hospital's decision maker as well as feedback about the patient's perception of service quality in order to maintain hospital patients and as the basis for periodic evaluations and initial step in assessing the quality of services to patients. The payment method of payment in the form of standalone services or use insurance seems to be influence the respondent's answers and can provide different analytical results, therefore, next researchers are expected to do better further research.